Respuesta :
Answer:
Below in bold.
Step-by-step explanation:
The identity is of the form
(a + b)^2 = a^2 + 2ab + b^2.
a) Sqrt 49 = 7 and we need + 28 as the middle coefficient . We get this with
2*7 + 2*7 so the first coefficient is 2*2 = 4.
So * = 4a^2.
(2a + 7)^2 = (2a + 7)(2a + 7) = 4x^2 + 14a + 14a + 49.
b) -6 * -6 = 36 -24 = 2*-6 + 2 *-6 so the last term is 4x^2
c) The middle term must be an 'ab' term.
sqrt 6.25 = 2.5 and sqrt 1/4 = 1/2
So the coefficient of the middle term is 2.5 * 1/2 + 2.5 * 1/2
= 2.5
So the middle term is 2.5ab.
d) The first term will be in b^2.
100 = 10* 10 and we need 2 as a middle term so coefficient of the first term
will be 1/100 or 0.01. as the 2 comes from 0.1 * 10 + 0.01 * 10 and (0.1)^2 = 0.01
So it is 0.01b^2.
Answer:
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:a2-2ab+b2 or a2+2ab+b2
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:a2-2ab+b2 or a2+2ab+b2since:
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:a2-2ab+b2 or a2+2ab+b2since:a2-2ab+b2 = (a-b)2
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:a2-2ab+b2 or a2+2ab+b2since:a2-2ab+b2 = (a-b)2 and
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:a2-2ab+b2 or a2+2ab+b2since:a2-2ab+b2 = (a-b)2 anda2+2ab+b2 = (a+b)2
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:a2-2ab+b2 or a2+2ab+b2since:a2-2ab+b2 = (a-b)2 anda2+2ab+b2 = (a+b)2 In the above equations, we have a trinomial being expressed as a square of a binomial.
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:a2-2ab+b2 or a2+2ab+b2since:a2-2ab+b2 = (a-b)2 anda2+2ab+b2 = (a+b)2 In the above equations, we have a trinomial being expressed as a square of a binomial.Knowing that the above equations are true, we can work with our given binomial and solve backwards from there:
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:a2-2ab+b2 or a2+2ab+b2since:a2-2ab+b2 = (a-b)2 anda2+2ab+b2 = (a+b)2 In the above equations, we have a trinomial being expressed as a square of a binomial.Knowing that the above equations are true, we can work with our given binomial and solve backwards from there:36–12x -> a = x, b = 6
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:a2-2ab+b2 or a2+2ab+b2since:a2-2ab+b2 = (a-b)2 anda2+2ab+b2 = (a+b)2 In the above equations, we have a trinomial being expressed as a square of a binomial.Knowing that the above equations are true, we can work with our given binomial and solve backwards from there:36–12x -> a = x, b = 6Because a = x, the monomial that we want to add to 36–12x is x2.
Since we want to add a single term (monomial) to the given binomial (36-12x) such that the resulting trinomial can be rewritten as the square of another binomial, then we want to make sure our resulting trinomials are of the following form:a2-2ab+b2 or a2+2ab+b2since:a2-2ab+b2 = (a-b)2 anda2+2ab+b2 = (a+b)2 In the above equations, we have a trinomial being expressed as a square of a binomial.Knowing that the above equations are true, we can work with our given binomial and solve backwards from there:36–12x -> a = x, b = 6Because a = x, the monomial that we want to add to 36–12x is x2.The resulting trinomial is: x2 -12x + 36 = (x-6)2